2019
DOI: 10.1371/journal.pone.0201329
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Shea tree (Vitellaria paradoxa) on maize and soybean production

Abstract: Vitellaria paradoxa provides many benefits to farmers within the Shea belt. However, increased threats to it necessitate its conservation, and one common approach is the practice of agroforestry. A number of studies have shown that Shea tree has influence on crop production, and yet, some of these studies were done using single season experiments or bioassays using mature Shea tree components. In this study, the seasonal influence of young and mature Shea trees on Maize and Soybean yields was invest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…Recently, [14] a field trial in Uganda demonstrated that soybean was significantly affected by intercropping with a deciduous tree, Vitellaria paradoxa, showing a yield reduction with respect to an open field cultivation, ranging from 39% to 46% when cultivated under the canopy of young and mature trees, respectively. Under humid, sub-tropical conditions in Brazil [13], it was shown that soybean yield parameters were affected by LA reduction in two agroforestry systems based upon eucalyptus and Peltophorum dubium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, [14] a field trial in Uganda demonstrated that soybean was significantly affected by intercropping with a deciduous tree, Vitellaria paradoxa, showing a yield reduction with respect to an open field cultivation, ranging from 39% to 46% when cultivated under the canopy of young and mature trees, respectively. Under humid, sub-tropical conditions in Brazil [13], it was shown that soybean yield parameters were affected by LA reduction in two agroforestry systems based upon eucalyptus and Peltophorum dubium.…”
Section: Discussionmentioning
confidence: 99%
“…To date, imported soybean meal for animal feeding (i) represents 70% of protein-rich feedstuff used in the European Union (EU) [8] and (ii) it is associated with an increase of environmental impacts generated by land clearing in South America [9]. Worldwide, soybean represents one of the largest sources of vegetable oil and animal protein feed [10].The effect of intercropping on soybean productivity has been studied under several agroforestry systems and in different biogeographic regions, resulting in different responses according to tree density when it comes to elements such as the competition for light, water and nutrients [11][12][13][14]. In particular, Reynolds [11] observed that, under temperate climate conditions, the reduction of light availability, more than the competition for soil water, caused a significant decline of the Net Assimilation of plants within a distance of 2 m from the tree rows.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The cultivation of crops such as maize and soybean is being used to generate income and to enhance food security in shea tree parklands. The authors of a study carried out in Uganda suggest that different responses have been observed regarding soybean and maize yields [144]. Due to the competition for light and nutrients, intercropping with mature shea trees led to very low maize and soybean yields compared with intercropping with young shea trees.…”
Section: Importance Of V Paradoxa In the Context Of Agroforestrymentioning
confidence: 99%
“…For generations, inhabitants have utilized this staple in numerous aspects of life: as a fatty oil for frying foods, in soap making, in cultural ceremonies, and in innovative TMs. 10 While shea butter has been documented as a TM therapy for conditions such as nasal congestion, hemorrhoids, and rheumatism; it is also used pervasively in the treatment of dermatoses in SSA. 11 To date, there exists a paucity of literature on the many uses of shea butter in treating cutaneous conditions in SSA.…”
Section: Introductionmentioning
confidence: 99%